Manajemen Sarana dan Prasarana Pendidikan Perspektif Ayat-Ayat Al-Qur’an - Muhammad Ibnu Faruk Fauzi; Hendri Yusuf (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article reviews the importance of management of educational facilities and infrastructure in the perspective of Qur'anic verses. The discussion of educational facilities and infrastructure is described as an integral part of education management, which includes various components such as curriculum, materials, methods, educators, students, and infrastructure. In this context, understanding of the role of facilities and infrastructure as a key factor in education is still somewhat lacking, which can hinder the learning process to be not optimal. This research uses a literature study method with an analytical-descriptive approach. The results of the study confirm that the management of educational facilities and infrastructure is a process that aims to manage and utilize all educational facilities and infrastructure effectively. The importance of infrastructure management is reinforced by views derived from verses of the Qur'an. The purpose of the management of educational facilities and infrastructure is to ensure that educational institutions are able to provide services professionally so that the learning process can take place effectively and efficiently. The implementation of management of educational facilities and infrastructure includes planning, organizing, implementing and utilizing, inventory, and supervision and maintenance. The conclusion of this study emphasizes that the management of educational facilities and infrastructure must be based on principles that ensure smooth learning activities in educational institutions.